Prevalence of modifiable risk factors and relation to stroke and death in patients with atrial fibrillation: A report from the China atrial fibrillation registry study. (17th October 2019) - Jiang, Chao; Lan, Di‐Hui; Du, Xin; Geng, Yan‐Ping; Chang, San‐Shuai; Zheng, Danni; Chen, Jin‐Bo; Yu, Rong‐Hui; Sang, Cai‐Hua; Long, De‐Yong; Tang, Ri‐Bo; Zhou, Ying‐Chun; et al.
Abstract: Background: Lifestyle and risk factor management may improve outcomes in patients with atrial fibrillation (AF). We aim to evaluate the prevalence of modifiable risk factors and how these factors impact clinical outcomes in patients with AF. Methods and Results: Data on 17 898 AF cohort patients with AF enrolled between 2011 and 2016 was analyzed. A healthy lifestyle was defined as not smoking, not drinking, a healthy body mass index (BMI), untreated total cholesterol less than 200 mg/dL, untreated blood pressure (BP) less than 120/80 mm Hg, and untreated fasting plasma glucose (FPG) less than 100 mg/dL. The association between risk factors and risk of the composite endpoint of all‐cause mortality and nonfatal ischemic stroke were assessed using Cox proportional hazards regression model. Only 4.0% of patients achieved a healthy lifestyle. In multivariate analysis, current smoking, a low BMI, not well‐controlled FPG were independently and significantly associated with higher risk of all‐cause mortality and nonfatal ischemic stroke, with corresponding hazard ratio (HR) estimates 1.22 (95% confidence interval [CI], 1.00‐1.47), HR = 1.72 (95% CI, 1.34‐2.20), and HR = 1.25 (95% CI, 1.06‐1.46), respectively. High BP was also associated with higher risk with the outcomes (HR = 1.15, 95% CI, 1.00‐1.34). Compared with patients with no risk factor, those who failed to maintained or achieved optimal risk factor control had a progressively higher risk of death and nonfatal ischemic stroke (HR for 1 risk factor = 1.44; 95% CI, 1.07‐1.92; and more than 2 risk factors =  1.75; 95% CI, 0.99‐3.09). Conclusions: Maintenance of well‐controlled risk factors may substantially lower the risk of death and ischemic stroke in patients with AF.